2018
DOI: 10.1063/1.5042344
|View full text |Cite
|
Sign up to set email alerts
|

Structural, magnetic, and magnetocaloric properties of Fe7Se8 single crystals

Abstract: The magnetocaloric effect has been studied in high quality single crystals of Fe7Se8 (3c type) grown by using Bridgman’s method. Magnetization and magnetocaloric effect measurements have been carried out in a magnetic field up to 5 T over the temperature range from 2 to 490 K. The spin reorientation transition from the easy c-axis to the easy c-plane, proceeding in an abrupt fashion, as a first-order phase transition, has been observed near the temperature TR ≈ 125 K. The magnetization curves in the vicinity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Phase analysis and structure determination were performed by x-ray powder diffraction using a Siemens D500 diffractometer equipped with a semiconductor high-resolution Si:Li detector. It was found that the studied crystal is a single-phase material with a 3c structure and the following lattice constants: a=b=7.245 Å and c=17.67 Å (P3 1 21 space group) [9]. The chemical composition of the crystals was verified by scanning electron microscopy (SEM)/energy-dispersive x-ray spectroscopy (EDX) techniques using an X-MAX Silicon Drift Detector with the scanning electron microscope JEOL JSM-7600F.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phase analysis and structure determination were performed by x-ray powder diffraction using a Siemens D500 diffractometer equipped with a semiconductor high-resolution Si:Li detector. It was found that the studied crystal is a single-phase material with a 3c structure and the following lattice constants: a=b=7.245 Å and c=17.67 Å (P3 1 21 space group) [9]. The chemical composition of the crystals was verified by scanning electron microscopy (SEM)/energy-dispersive x-ray spectroscopy (EDX) techniques using an X-MAX Silicon Drift Detector with the scanning electron microscope JEOL JSM-7600F.…”
Section: Methodsmentioning
confidence: 99%
“…The SR transition in the samples with the 3c structure occurs at∼125 K. The magnetic and magnetocaloric properties of these crystals have been presented in Refs. [9,10]. The magnetocaloric effect in Fe 7 Se 8 has attracted interest because of the existence of a normal MCE above the spin reorientation temperature T SRT for B || c and an inverse magnetocaloric effect below the T SRT for B ⊥ c [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Fe 7 Se 8 is one of the few systems possessing spin reorientation (the easy axis changes from the c-plane toward the c-axis at about 130 K), which is expected to have a large magnetocaloric effect in a wide temperature range. 13 However, the controllable synthesis of 2D nonstoichiometric Fe 7 Se 8 with accurate composition and high quality still faces great challenges. First, it is easy to introduce other impurities with different stoichiometric ratios, such as FeSe, Fe 3 Se 4 , and FeSe 2 .…”
mentioning
confidence: 99%
“…Notably, Fe-based chalcogenides have received significant attention due to the intriguing discoveries of superconductivity and magnetism. Fe 7 Se 8 was demonstrated to be ferrimagnetic with a high Néel temperature of 455 K, showing great application prospects in the field of RT spintronic devices. In addition, Fe 7 Se 8 is one of the few systems possessing spin reorientation (the easy axis changes from the c -plane toward the c -axis at about 130 K), which is expected to have a large magnetocaloric effect in a wide temperature range . However, the controllable synthesis of 2D nonstoichiometric Fe 7 Se 8 with accurate composition and high quality still faces great challenges.…”
mentioning
confidence: 99%